Aedes albopictus of Paris (France) is competent to transmit at least three of the four dengue virus serotypes - Chloé Bohers; Marie Vazeille; Luidji Pascalin; Kevin Meignan; Anaïs Karch; Xavier De Lamballerie; Xavier De Lamballerie; Anna-Bella Failloux (Frontiers in Tropical Diseases)
We report that Aedes albopictus Paris collected in June 2023 were experimentally able to transmit at least three dengue virus (DENV) serotypes, from 14 days post-infection (dpi) for DENV-3 and DENV-4, and from 21 dpi for DENV-2. Given the growing number of dengue autochthonous cases reported in France, episodes of active transmission in Paris are expected as it was reported in 2023 in the greater Paris area.